Substrate profiling of marine-derived thermotolerant cysteine protease reveals unique cleavage preferences for industrial applications - Victoria Røyseth; Brianna M. Hurysz; Hasan Arsın; Julia M. Vazquez; Anna-Karina Kaczorowska; Anita-Elin Fedøy; Daria Biernacka; Sebastian Dorawa; Tadeusz Kaczorowski; Runar Stokke; Anthony J. O’Donoghue; Ida Helene Steen (Scientific Reports)
Abstract Due to their industrial importance, new proteases are constantly being sourced from the marine environment. However, their substrate specificities remain insufficiently studied, restricting the evaluation of their potential applications. Here, we applied multiplex substrate profiling by mass spectrometry (MSP-MS) to globupain, a marine thermotolerant clostripain-like protease and show that it has a novel substrate specificity. Globupain is an endopeptidase with a preference for cleavage of substrates on the C-terminal side of norleucine (Nle), Leu, Asn, Arg and Lys. While it can hydrolyze gelatin and collagen, its reaction rate is lower than that of papain, a commercial cysteine protease. The precise knowledge of substrate specificity of globupain led to the discovery that the calpain inhibitors MG101 and leupeptin inactivate globupain activity with IC50 values of 23.79 and 138.7 nM, respectively. Further investigation of additive effects revealed that globupain activity was stimulated by Triton X-100 and Tween 40 at concentrations of up to 1%. Globupain exhibited tolerance to elevated DTT concentrations and retained most of its activity in the presence of Mg2+ or Mn2+ compared to its preferred cation, Ca2+. In conclusion, globupain is a novel clostripain-like cysteine protease with a distinct substrate cleavage profile and remarkable stability in the presence of various additives, highlighting its potential for industrial applications.